1989
DOI: 10.1007/bf00441511
|View full text |Cite
|
Sign up to set email alerts
|

Unchanging clinical picture of coeliac disease presentation in Campania, Italy

Abstract: Four hundred and sixty-three new diagnoses of coeliac disease in children were made during 1973 to 1986 in our department. The distribution of new diagnoses per year did not show any decreasing trend in the period 1973 to 1986. No changing trend in breast feeding attitudes was found in the region during the same period. Analysis of the clinical pattern showed a constant distribution of age at diagnosis, onset of first symptoms and nature of symptoms throughout the period studied. These data suggest that coelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…both in children (M) and in adults (6, 7). a figure similar to those reported by other European countries (8)(9)(10). even though rates of 1 : 597 have been found in Ireland (1 1 ) and 1 : 10.000 among Danish children (12).…”
Section: Prevalence and Clinical Significance Of Gliadin Antibodies Isupporting
confidence: 80%
“…both in children (M) and in adults (6, 7). a figure similar to those reported by other European countries (8)(9)(10). even though rates of 1 : 597 have been found in Ireland (1 1 ) and 1 : 10.000 among Danish children (12).…”
Section: Prevalence and Clinical Significance Of Gliadin Antibodies Isupporting
confidence: 80%
“…Differing changes in incidence rates of CCD have also been reported since the second half of the 1970s: decreasing (3,6,(14)(15)(16)(17), increasing (5,11,12), or unchanged (7,9,13). During the same time a shift in presenting features towards milder and uncharacteristic symptoms has been reported in children (7,18) and adults (19,20).…”
mentioning
confidence: 83%
“…Recent studies in childhood coeliac disease (CCD) have disclosed highly varying incidence rates by birth (between 0.09 and 2.93: lOOO), even in closely related geographic areas (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Differing changes in incidence rates of CCD have also been reported since the second half of the 1970s: decreasing (3,6,(14)(15)(16)(17), increasing (5,11,12), or unchanged (7,9,13).…”
mentioning
confidence: 91%
“…Recent reports have suggested that the incidence of coeliac disease is decreasing in the UK and Ireland [13,14], increasing in Sweden [15] and has remained stable in Finland [26], Italy [27] and Spain [28]. These variations could be due to changes in diagnostic procedures [29] or defective retrieval of data.…”
Section: Discussionmentioning
confidence: 99%
“…22] The types of evidence used in reaching a diagnosis of coeliac dis ease in Leicestershire between 1975 and1989. formed the basis of diagnosis in children under 14 years old: (a) ab sent or almost absent villi on normal diet; (b) mucosa returning to normal on gluten-free diet; (c) positive challenge test, (d) formal rechallcnge tests are often considered unpleasant by clinicians and are often not put into practice [22,23]. It was frequently considered unnecessary either because of a very strong family history of coeliac disease or there had been a positive third and even fourth biopsy following relapse on intentional or unintentional exposure to gluten.…”
Section: Diagnostic Criteriamentioning
confidence: 99%